Rede de logística reversa para os resíduos sólidos urbanos - Ferri, Giovane Lopes (2016)
With the growing number of businesses worldwide and the immense amount of goods transported daily, also increases the amount of solid waste (SW) generated and materials that need to be sent back to its origin. Reverse logistics is the area responsible for this reverse flow of products, which is based both on current legislation, as the possibility to add value or reduce costs for the management of waste. Therefore, its implementation is a course element to the sustainable development of the planet because it enables the reuse and reduction in consumption of raw materials. In Brazil, the impetus to this specialized area of logistics, occurred from the institution of the National Solid Waste Policy (Law No. 12.305 / 2010) whose objectives, among others, are set shared responsibilities, implement the selective collection and reverse logistics in the country, promoting the optimization as the use and adequacy of SW. To enable this policy, it is necessary that landfills are designed and made possible through the selective collection that extends the useful life of landfills. Thus, this paper aims to carry out mathematical modeling of SW reverse logistics network enabling structure a reverse logistics network SW to meet current legislation, economically and socially viable. The model was applied in São Mateus-ES and Espírito Santo generating two distinct scenarios, state and local scales. This dissertation exposes an original application of this mathematical in so far as this modeling makes possible the opening of facilities in two different layers that are communicated between themselves, besides having an internal flow of reallocation of residues in the second layer.